EXPERIMENTAL RESEARCH INTO DYNAMIC PROPERTIES OF MASONRY BARREL VAULTS NON-REINFORCED AND REINFORCED WITH CARBON COMPOSITE STRIPS - Radek Ziegler; Jiří Witzany; Daniel Makovička; Shota Urushadze; Stanislav Pospíšil; Jan Kubát; Klára Kroftová (Civil Engineering Journal, 2016)
The study of dynamic behaviour of vaults of historic buildings reveals new knowledge which can be used for the local analysis and stabilisation and rehabilitation designs of damaged vaulted structures. The analysis of the results of dynamic loading brings objective background material for the identification and localisation of failures according to MAC or COMAC criteria [1, 2] and the assessment of serviceability and structural reliability of vaulted structures of historic buildings .